In Vitro Metabolic Stability and Permeability of Gymnemagenin and Its In Vivo Pharmacokinetic Correlation in Rats – A Pilot Study - Bera, Rammohan; Kundu, Amit; Sen, Tuhinadri; Adhikari, Dipan; Karmakar, Sanmoy (Planta Medica, 2016)
Gymnema sylvestre is traditionally used for diabetes mellitus. A literature survey revealed very few reports, particularly on rat liver microsomal stability, caco-2 permeability and efflux concerns and its correlation with the bioavailability of gymnemagenin, an important component of G. sylvestre. Therefore, the objective of our study was to investigate the in vitro rat liver microsomal stability and caco-2 permeability along with the efflux of gymnemagenin and establish a probable correlation of these in vitro findings with pharmacokinetic parameters after oral and intravenous administration in rats.Rat liver microsomal stability studies to estimate the in vitro intrinsic half-life, clearance, and Caco-2 permeability after 21 days of culture to determine the apparent permeability from apical to basal and from basal to apical, and efflux ratio of gymnemagenin were performed using liquid chromatography-tandem mass spectrometry. A sensitive, robust bioanalytical method was validated and successfully applied to determine the plasma exposure of gymnemagenin.In vitro rat liver microsomal stability demonstrated that gymnemagenin metabolizes rapidly with a short apparent and intrinsic half-life (~ 7 min) and high intrinsic clearance, i.e., 190.08 µL/min/mg of microsomes. The results of the Caco-2 study indicated a poor permeability (1.31 × 10− 6 cm/sec) with a very high efflux ratio. The pharmacokinetic study revealed poor oral bioavailability (~ 14 %) of gymnemagenin and it was found to have a short half-life and a high clearance in rats. Our in vitro findings indicated low metabolic stability and poor Caco-2 permeability with high efflux, which might have a role in the observed poor oral bioavailability in rats.
Keywords: Gymnema sylvestre; Asclepiadaceae; gymnemagenin; rlm; Caco-2; pharmacokinetics; LC-MS/MS